Development Direction of Muara Gembong Coastal Area Based on Abrasion Vulnerability Analysis - Firman, Firman; Kasman, Kasman; Zefri, Zefri (SEAN Institute, 2020)
Abrasion in Muara Gembong District has resulted in changes in the coastline, reaching 3,852 m. Abrasion causes physical, environmental, social, and economic changes, as well as changes in the lives of local people. This study aims to analyze the level of vulnerability due to abrasion in the coastal area of Muara Gembong. This study uses the AHP method to determine the weight of factors influencing vulnerability due to abrasion by involving stakeholders as respondents. Giving value weights to criteria and alternatives, then pairwise comparisons of each stakeholder's opinions. Using proximity analysis techniques, vulnerability zone analysis was carried out using kernel density analysis techniques and analysis regarding the distance from the coast to settlements. The analysis technique using Weighted Overlay is carried out to determine the vulnerability zone based on the results of the factor weight assessment. From the results of the analysis, the factor that has the greatest influence on the vulnerability of the Muara Gembong coastal area due to abrasion is the environmental factor; this shows that if there is environmental damage, especially damage to protected forests and mangrove forests, it will accelerate the process of coastal abrasion. The analysis results show that 85.10% of the coastal area of Muara Gembong is in the moderate vulnerability zone, 14.25% is in the high vulnerability zone, and 0.65% is in the low vulnerability zone. The results of the superimpose between the spatial pattern plan of Muara Gembong District and the Vulnerability Map show that the directions for developing activities for cultivation areas dominated by residential activities are in high and medium vulnerability zones. In contrast, low vulnerability zones are directed toward developing non-settlement cultivation areas.